In vitro multiplication of the rare and endangered slipper orchid, Paphiopedilum rothschildianum (Orchidaceae) - Ng, Chyuam Yih; Mohd. Saleh, Norihan; Qamaruz Zaman, Faridah (Academic Journals, 2010)
Paphiopedilum rothschildianum is an endangered orchid species endemic to Mount Kinabalu, Sabah, and Malaysia. The vegetative propagation of this plant has always been restricted due to its slow growth and maturation rates. Thus, an in vitro tissue culture technique was explored in order to overcome this limitation. In this study, clonal propagation of P. rothschildianum was achieved through in vitro formation of multiple shoots from stem nodal and single shoot explants cultured onto halfstrength Murashige and Skoog medium. The responses of the explants to the presence of different types of organic nitrogen additives viz. casein hydrolysate, peptone and tryptone-peptone (in amount of 0.5, 1.0 and 2.0 g/l) in the culture medium were also evaluated. The addition of these organic nitrogen additives into the basal medium slightly enhanced the number of multiple shoots formed on both types of explants when compared to additive-free MS medium. After 16 weeks of culture, an average of 2.9 shoots per stem nodal explant and 2.8 shoots per single shoot explant were obtained on half-strength MS medium supplemented with 1.0 g/l peptone and 2.0 g/l tryptone-peptone, respectively. All the newly-formed shoots were divided into single plantlets and subcultured onto similar respective medium. After an additional 12 weeks of culture on the same medium, plantlets with 3 - 4 roots were acclimatized and transferred to a glass house where they showed 90% survival rate. Thus, the method presented in this study had provided a promising strategy for the production of large numbers of phenotypically stable P. rothschildianum.